METHODOLOGY FOR THE EXPERIMENTAL IMPLEMENTATION OF LIME-WASTE-BASED GYPSUM CONCRETE (Spectrum Journal of Innovation, Reforms and Development, 2026)
The present study investigates the methodology for the production of gypsum concrete based on lime waste and Redispersible Polymer Powder (RPP), together with the assessment of its technical and economic efficiency. Experimental gypsum concrete compositions containing different amounts of lime waste and RPP were prepared and tested under controlled curing conditions. The introduction of lime waste and RPP made it possible to reduce gypsum consumption by up to 25% while maintaining high strength and density of the gypsum concrete products. The optimum preparation procedure included sequential mixing of lime waste, RPP additive, and G-6 grade gypsum under controlled mixing speeds and curing conditions. Economic analysis showed that the modified gypsum concrete has a lower production cost compared with conventional gypsum concrete. The economic benefit from producing 1 m³ of gypsum concrete under industrial conditions amounted to 91,940 UZS, while the projected annual economic effect reached 1,654,920,000 UZS. The developed composition was successfully tested under the production conditions of Ferghana Ceramics Industry LLC and demonstrated improved durability, reduced binder consumption, and enhanced structural performance.